First‐in‐man safety and pharmacokinetics of synthetic ozonide OZ439 demonstrates an improved exposure profile relative to other peroxide antimalarials. (10th January 2013) - Moehrle, Joerg J.; Duparc, Stephan; Siethoff, Christoph; van, Paul L. M.; Craft, J. Carl; Arbe‐Barnes, Sarah; Charman, Susan A.; Gutierrez, Maria; Wittlin, Sergio; Vennerstrom, Jonathan L.
<x xml:space="preserve">Abstract</x> Aims To assess the safety and pharmacokinetics of a new synthetic ozonide antimalarial, OZ439, in a first‐in‐man, double‐blind study in healthy volunteers. Methods OZ439 was administered as single oral daily doses of a capsule formulation (50–1200 mg) or an oral dispersion (400–1600 mg, fed and fasted states) and for up to 3 days as an oral dispersion (200–800 mg day−1). Plasma concentrations of OZ439 and its metabolites were measured by LC‐MS. Results The pharmacokinetic (PK) profile of OZ439 was characterized by a tmax of around 3 h, followed by a multiphasic profile with a terminal half‐life of 25–30 h. The PK parameters were approximately dose proportional for each group and profiles of the metabolites followed a similar pattern to that of the parent compound. Following dosing for 3 days, accumulation was less than two‐fold but steady‐state was not achieved. In the presence of food, no effect was observed on the t1/2 of OZ439 while the exposure was increased by 3 to 4.5‐fold. Exposure was higher and inter‐subject variability was reduced when OZ439 was administered as an oral dispersion compared with a capsule. The urinary clearance of OZ439 and its metabolites was found to be negligible and OZ439 did not induce CYP3A4. The antimalarial activity profiles of a subset of serum samples suggested that the major antimalarial activity originated from OZ439 rather than from any of the metabolites. Conclusion The safety and pharmacokinetic profile of OZ439 merits progression to phase 2a proof of concept studies in the target population of acute uncomplicated malaria.